Enhanced Indonesian Throughflow heat transport prolongs the recharge process during triple La Niña events - Ziyang Cao; Mingting Li; Arnold L Gordon; Dongxiao Wang (Environmental Research Letters)
The Indonesian Throughflow (ITF) serves as the only tropical branch of the Great Ocean Conveyer Belt, and plays an important role in Indo-Pacific Basin interactions. By calculating the heat budget during single and triple La Niña events (1973–1976, 1998–2000, 2020–2023), we quantified the contribution of enhanced ITF heat transport to prolonging the recharge process during triple La Niña events. During triple La Niña events, the accumulated heat transported by the ITF is about −15.01 ZJ (more than twice that for single events), nearly offsetting the positive contribution of net heat flux from the atmosphere over the Pacific Ocean. Single La Niña events are confined to thermal processes within the Pacific Ocean, while triple events are products of basin interactions, and the ITF serves as a crucial oceanic link between the tropical Indian and Pacific Oceans. The enhanced heat transport of the ITF is concentrated in the subsurface layer (100–200 m), significantly during the second year of a triple La Niña event. The accumulation of enhanced ITF heat transport in the subsurface layer effectively expands the recharge–discharge area from the western Pacific to the eastern Indian Ocean, with the ensuing discharge process of the tropical Indian Ocean along with sustained La Niña conditions in the Pacific Ocean.